Optimization of self-nano emulsifying drug delivery system of rifampicin for nebulization using cinnamon oil as oil phase - Ricardo, I Komang Aan Adi; Arimurni, Dewa Ayu (Universitas Ahmad Dahlan, 2024)
Lung delivery can overcome the problems related to the effectiveness of tuberculosis treatment by increasing the drug concentration at the target site. Rifampicin as the first-line antibiotic for tuberculosis has low water solubility and is unstable in gastric which hinders its effectiveness. Self-nanoemulsifying drug delivery system (SNEDDS) is a strategy known to improve the solubility and stability of such drugs. This study aimed to obtain the optimum formula of rifampicin SNEDDS intended for lung nebulization using essential oil as an oil phase. Several essential oils are known to have effective antibacterial on Mycobacterium tuberculosis. However, a high capability to solubilize the drug is required for SNEDDS formulation. Cinnamon oil, tween 80, and transcutol P were chosen as SNEDDS components for optimization using a D-optimal mixture based on the physicochemical characteristics. The optimum formula comprised 12.65% cinnamon oil, 75.00% tween 80, and 12.35% transcutol P which dispersed easily to form a highly transparent emulsion in normal saline under 1 minute. Upon dilution with saline, the optimal SNEDDS can produce a homogenous nanometer droplet (169.2±19.771 nm, PDI of 0.258±0.070) with acceptable pH for lung administration. It also has a viscosity similar to water (0.94±0.01 cP) which allows it to be nebulized easily (aerosol output rate of 0.14±0.02 g/min). Although the diluted SNEDDS has a zeta potential of -2.533±0.268 mV, it was stable for up to 4 hours during the nebulization. These results indicate the potential of cinnamon oil-based rifampicin SNEDDS to be an alternative in the pulmonary delivery of rifampicin via nebulization.